Muslim women in Nigeria between postmodern feminism and religious fanaticism: the case of the Islamic law (2007)
In this paper, the Islamic activism of Muslim women in contemporary Nigerian society has been analyzed. The paper examines the position of Muslim women and the reaction of these women to the re-introduction of the criminal aspects of the Shari'ah law in Nigeria. It begins by recapitulating the development of feminism in postmodem society and the position of Muslim women described as Islamic feminists. There are many philosophical definitions and perspectives in the feminist movement that show that it is not spurious or baseless to wish away the version known as Islamic Feminism but rather demands serious study This article argues that despite the sheer diversity in the philosophical backgrounds of those who debate the role and empowerment of women within the Islamic tradition, it is no longer possible to deny the feminist movement for women's emancipation which is ultimately focused on gaining for women in practical terms all the rights that they have been denied. The paper therefore focuses on the role of Muslim women in the development of shari'ah implementation in Nigeria as part of their feminist struggle for Muslim women political emancipation and how the feminist aspirations of these women in respect of what they perceive as a destructive and overzealous implementation of the shari’ah law can be realizable. This study reveals that Nigeria has failed in the state implementation of the shari'ah and submits that there is a need to adopt the use of forensic evidence to make the Islamic law gender compliant as envisaged by Allah-the lawmaker.